2021
DOI: 10.5737/23688076314470475
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of self-management strategies used by young adults who have undergone hematopoietic stem cell transplantation: A narrative review

Abstract: Hematopoietic stem cell transplantation is frequently used to treat young adults with hematologic cancer. The treatment can cause a range of side effects that require patients to self-manage their symptoms. However, there do not seem to be any studies that review the literature on self-management strategies used by this group. The purpose of this paper is to summarize the self-management strategies used by young adults (18–39 years old) who have received a hematopoietic stem cell transplant for leukemia or lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…During transplantation, the patients placed themselves in the role of the "weak" subconsciously and lost their autonomy. Nurses play a key role in helping patients acquire self-management strategies by providing information about symptom management, helping them manage their emotions, and encouraging them to be actively involved in their care [24]. Studies have demonstrated the feasibility and effectiveness of this self-management modality in HSCT patients during hospitalization [24,42].…”
Section: Discussionmentioning
confidence: 99%
“…During transplantation, the patients placed themselves in the role of the "weak" subconsciously and lost their autonomy. Nurses play a key role in helping patients acquire self-management strategies by providing information about symptom management, helping them manage their emotions, and encouraging them to be actively involved in their care [24]. Studies have demonstrated the feasibility and effectiveness of this self-management modality in HSCT patients during hospitalization [24,42].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized clinical trial conducted in the USA also used videos with young adults to encourage self-management and help focus on the elements that he considers most important in his life. Such a strategy can be considered a source of support during HSCT 40 . On the other hand, internet access is still selective, and disfavors poorer social classes and people with little education.…”
Section: Educational Technologies Dependent On Electronic Media/devic...mentioning
confidence: 99%
“…Akbulut et al (20) Os pacientes devem ser estimulados ao autocuidado e autogestão de sua condição de saúde-doença ainda no internamento hospitalar, para que não tenham dificuldade em seguir as orientações dispensadas. Tratando-se do TCTH, este tratamento exige que pacientes e familiares/cuidadores sejam capazes de colaborar para uma assistência efetiva, seguindo as orientações de cuidado, para que seja possível minimizar os riscos e ter uma melhor qualidade de vida (31) , desde os cuidados de si até o manejo correto de complicações.…”
Section: Nível De Evidênciaunclassified